Age‐related changes in the energy of human mesenchymal stem cells. Issue 3 (17th November 2021) - Barilani, Mario; Lovejoy, Christopher; Piras, Roberta; Abramov, Andrey Y.; Lazzari, Lorenza; Angelova, Plamena R.
Abstract: Aging is a physiological process that leads to a higher risk for the most devastating diseases. There are a number of theories of human aging proposed, and many of them are directly or indirectly linked to mitochondria. Here, we used mesenchymal stem cells (MSCs) from young and older donors to study age‐related changes in mitochondrial metabolism. We have found that aging in MSCs is associated with a decrease in mitochondrial membrane potential and lower NADH levels in mitochondria. Mitochondrial DNA content is higher in aged MSCs, but the overall mitochondrial mass is decreased due to increased rates of mitophagy. Despite the higher level of ATP in aged cells, a higher rate of ATP consumption renders them more vulnerable to energy deprivation compared to younger cells. Changes in mitochondrial metabolism in aged MSCs activate the overproduction of reactive oxygen species in mitochondria which is compensated by a higher level of the endogenous antioxidant glutathione. Thus, energy metabolism and redox state are the drivers for the aging of MSCs/mesenchymal stromal cells. Abstract : Aging in mesenchymal stem cells (MSCs) is associated with a decrease in mitochondrial membrane potential and NADH levels. Mitochondrial DNA content is higher in aged MSC, but the overall mitochondrial mass is decreased due to increased rates of mitophagy. Despite the higher level of ATP in aged cells, a higher rate of ATP consumption renders them more vulnerable to energy deprivation compared to younger cells.